ANALISIS USABILITY GOOGLE CLASSROOM SEBAGAI PLATFORM E-LEARNING PADA PROGRAM STUDI PG PAUD FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MEDAN - Srinahyanti Srinahyanti; May Sari Lubis; Winda Widya Sari (FIP Unimed, 2021)
Google Classroom is one of The Google services provided for online learning. The PG PAUD (Pendidikan Guru Pendidikan Anak Usia Dini) Study Program has used it but not yet known how useful it is in online learning.This study aims to determine the Usability of Google Classroom. Usability concerning the use of the system. Usability can be measure through parameters using the USE Questionnaire. The device uses three parameters, namely Usefulness, Satisfaction, and Ease of Use consist of 30 questions filled in by PG PAUD students using the google form. The results showed that this system as a whole has good usability and was successful in facilitating and assisting the user to carry out their duties efficiently. Some of the weaknesses lie in the storage element, especially in files that are too large. Besides that, It can't use Voice notes. Users also expect several additional facilities, such as unlimited storage in Google Classroom, developers can provide an alternative in improving the check plagiarism attribute for each type of classwork. This recommendation expected will improve the usability of Google Classroom in the future. The novelty in research is explaining Google Classroom as the first platform used during this pandemic